2022
DOI: 10.1161/jaha.122.026493
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Objective and Perceived Social Isolation on Cardiovascular and Brain Health: A Scientific Statement From the American Heart Association

Abstract: Background Social isolation, the relative absence of or infrequency of contact with different types of social relationships, and loneliness (perceived isolation) are associated with adverse health outcomes. Objective To review observational and intervention research that examines the impact of social isolation and loneliness on cardiovascular and brain health and discuss proposed mechanisms for observed associations. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
67
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 93 publications
1
67
0
Order By: Relevance
“… 6 Several recent studies showed that both aspects of social disconnection, 20 , 24 , 25 social isolation only, 7 or loneliness only 8 , 26 were associated with the risk of incident CVD. These inconsistent findings were possibly caused by the variations in social network measurements, 3 age group, 7 sample size, and definition of the CVD across these studies. Our study offsets the limitations of some previous studies, such as having a limited number of HF events 7 or lack of direct comparisons of social isolation and loneliness in the same study setting.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“… 6 Several recent studies showed that both aspects of social disconnection, 20 , 24 , 25 social isolation only, 7 or loneliness only 8 , 26 were associated with the risk of incident CVD. These inconsistent findings were possibly caused by the variations in social network measurements, 3 age group, 7 sample size, and definition of the CVD across these studies. Our study offsets the limitations of some previous studies, such as having a limited number of HF events 7 or lack of direct comparisons of social isolation and loneliness in the same study setting.…”
Section: Discussionmentioning
confidence: 84%
“…1 Social isolation and loneliness have been recently recognized as important psychosocial determinants of cardiovascular diseases (CVDs), especially during the COVID-19 pandemic. 2 , 3 “Social isolation” refers to being objectively alone or having infrequent social connections, whereas “loneliness” is defined as a painful feeling caused by a discrepancy between one’s desire for connections and the actual degree of connections. 4 , 5 Despite compelling evidence linking social isolation and loneliness to multiple cardiovascular outcomes and premature mortality, less is known about their association with HF.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise referred to as distributed health literacy, a limited sphere of contact reduces the health literacy resources that can be used by patients, who themselves have low health literacy [ 73 ]. Compounding this further, isolation and loneliness can independently adversely affect their health [ 74 , 75 ]. Restrictions imposed during the COVID-19 pandemic highlighted the impact that isolation has on health outcomes [ 76 ], and provoked thought as to how isolated people can be reached and supported (e.g., telehealth) [ 76 , 77 , 78 , 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…2 , 3 Social isolation and loneliness have increasingly been suggested as risk factors for cardiovascular disease. 4 …”
mentioning
confidence: 99%